XIV. International Conference on Logistics in Agriculture 2020: Conference Proceedings (University of Maribor Press, 2020)
XIV. International Conference on Logistics in Agriculture 2020: Conference Proceedings. The 14th International Conference on Logistics in Agriculture, which has been organized by the Municipality of Sevnica, Grm Novo mesto - Biotechnology and Tourism Center, Faculty of Logistics, University of Maribor, Landscape Governance College GRM and Cooperative Union of Slovenia has this year’s central theme the Climate Change in Logistics in Agriculture. The conference has become traditional and pays attention to the ways for different views of logistics in connection with agriculture. That is why we/the organizers have invited lecturers on the topic Impact of climate change in agriculture. This year we will have on line conference due to coronavirus.